Development of Learning Module for Observation Report During the Covid-19 Pandemic - Besliana Afriani Siagian; Nurhayati Sitorus; Christina Sitepu (IKIP PGRI Bojonegoro, 2022)
Abstract: Innovation of education is needed to ensure effective online learning practices during the pandemic. It is necessary to avoid the accumulation of assignments without sufficient materials. Material needs must be met, for that a module is needed. this R&D-based study was conducted to determine the feasibility of the learning module. The research subject were several students from SMA Negeri 14, SMA Yapim, SMA Negeri 21, SMA Nasrani 3, and SMA Advent Air Bersih in Medan. Data were collected using a 4-D model and the results showed that the module was feasible to be used as indicated by the validation and try out score from lecturers, teachers, and students got score above 75%. Keywords: module; online learning; observation report Abstrak: Inovasi pendidikan sangat dibutuhkan untuk mengefektifkan pembelajaran online di masa pandemi. Pembelajaran online perlu menghindari menumpuk tugas tanpa materi yang cukup. Kebutuhan akan materi harus terpenuhi, untuk itulah diperlukan modul. Penelitian ini berbasis research and development bertujuan untuk mengetahui kelayakan modul pembelajaran. Subjek penelitian adalah sejumlah siswa di Kota Medan, yakni SMA Negeri 14 Medan, SMA Yapim Medan, SMA Negeri 21 Medan, SMA Nasrani 3 Medan, SMA Advent Air Bersih. Teknik pengumpulan data menggunakan model 4-D dan hasil penelitian menunjukkan bahwa modul layak digunakan dilihat dari hasil uji validasi dan uji coba terhadap dosen ahli, guru, dan siswa memperoleh nilai di atas 75 %. Kata Kunci: modul; pembelajaran online; laporan hasil observasi